Photoexcited fullerene C60 disturbs prooxidant‐antioxidant balance in leukemic L1210 cells. Issue 2 (13th March 2013) - Grynyuk, I.; Grebinyk, S.; Prylutska, S.; Mykhailova, A.; Franskevich, D.; Matyshevska, O.; Schütze, C.; Ritter, U.
Abstract According to the data of laser‐correlation spectroscopy of the pristine fullerene C60 water colloid solution used in the study the average hydrodynamic radius of nanoparticles was 50 nm and no agglomeration was observed. With the use of the fluorescent probe 2′, 7′‐dichlorofluorescein the production of reactive oxygen species (ROS) in rat thymocytes and in human leukemic cells L1210 pretreated with 10–5 M fullerene C60 and irradiated in a diapason 320–600 nm was estimated. Irradiation per se is shown to be followed by slight increase of ROS production. No further increase of fluorescent signal was detected in thymocytes during 3 h of incubation after combined action of C60 and irradiation. In contrast leukemic cells respond to combined action of C60 and irradiation by pronounced intensification of ROS production. This phenomenon is shown to be connected with prooxidant‐antioxidant imbalance induced by photoexcited fullerene C60 in L1210 cells, enhancement of the first superoxide dismutase against decreasing of the second glutathione peroxidase steps of antioxidant defense. The prooxidant effect of photoexcited fullerene C60 leading to oxidative stress could be used for elaborating the strategies of targeted oxidative injury of leukemic cells.